Hypoglycemic Effects of Fruit Extracts of Murraya Koenigii (L) In Streptozotocin Induced Diabetic Rats - Waghmare, Atish N; Tembhurne, Sachin V.; Sakarkar, Dinesh M. (Asian Journal of Pharmaceutical Research and Development, 2015)
Murraya koenigii leaves (Rutaceae) is used traditionally in Indian Ayurvedic system to treat diabetes. The aim of the present study was to evaluate the antidiabetic activity of ethanolic extract of Murraya koenigii fruits (MKF) in streptozotocin induced diabetic rats. Effect of oral administration of MKF (200 and 400 mg/kg) on the level of blood glucose, thiobarbituric acid reactive substances (TBARS), total cholesterol, triglycerides and glycogen were estimated. Glibenclamide was used as a standard drug. The elevated level of blood glucose, triglycerides and cholesterol were observed in diabetic rats while after treatment with MKF for 15 days normalized the values demonstrates the hypoglycemic activity. Decrease in glycogen in diabetic animal, suggests that the drug treatment promote the process of glycogenesis. Increase in the TBARS level in diabetic animals indicates to raise the level of lipid peroxidation which is a marker of oxidative stress while the treatment with MKF significantly (p<0.05) decreased the TBARS level indicated contributing protective antioxidant activity in diabetic animals. The ethanolic extract of M. koenigii possessed potent antioxidant properties which may be due to the presence of carbazole alkaloids. Thus the antidiabetic activity of M. koenigii leaves was probably due to the presence of its antioxidant property. ><0.05) decreased the TBARS level indicated contributing protective antioxidant activity in diabetic animals. The ethanolic extract of M. koenigii possessed potent antioxidant properties which may be due to the presence of carbazole alkaloids. Thus the antidiabetic activity of M. koenigii leaves was probably due to the presence of its antioxidant property.